2004
DOI: 10.1038/nn1302
|View full text |Cite
|
Sign up to set email alerts
|

Aβ is targeted to the vasculature in a mouse model of hereditary cerebral hemorrhage with amyloidosis

Abstract: The E693Q mutation in the amyloid beta precursor protein (APP) leads to cerebral amyloid angiopathy (CAA), with recurrent cerebral hemorrhagic strokes and dementia. In contrast to Alzheimer disease (AD), the brains of those affected by hereditary cerebral hemorrhage with amyloidosis-Dutch type (HCHWA-D) show few parenchymal amyloid plaques. We found that neuronal overexpression of human E693Q APP in mice (APPDutch mice) caused extensive CAA, smooth muscle cell degeneration, hemorrhages and neuroinflammation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
341
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(373 citation statements)
references
References 52 publications
24
341
1
2
Order By: Relevance
“…Total A␤ levels were determined on 10 -20% Novex Tricine Gels using Novex Tricine sample buffer including reducing agent (Invitrogen). To determine A␤40 and A␤42 levels, 10% bicineTris, 8 M urea SDS/PAGE was used as described previously (43). To measure A␤ concentrations on wires, the wires were heated in 100 L of sample buffer in a 1.5-mL microfuge tube at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total A␤ levels were determined on 10 -20% Novex Tricine Gels using Novex Tricine sample buffer including reducing agent (Invitrogen). To determine A␤40 and A␤42 levels, 10% bicineTris, 8 M urea SDS/PAGE was used as described previously (43). To measure A␤ concentrations on wires, the wires were heated in 100 L of sample buffer in a 1.5-mL microfuge tube at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The wires were either heated in PBS at 95°C for 10 min or plasma-sterilized before implantation. To do this, the wires were sealed in a STERRAD Tyvek pouch and sterilized in a STERRAD 100 S hydrogen peroxide gas plasma sterilizer (Advanced Sterilization Products) using the routine long cycle as programmed by the manufacturer (43). The wires were then implanted unilaterally into the hippocampus using a stereotaxic apparatus (AP, Ϫ2.5 mm; L, ϩ2.0 mm; DV, Ϫ1.8 mm).…”
Section: Stereotaxic Injection Of Extract Into Different Brainmentioning
confidence: 99%
“…An earlier theory suggested that A in CAA directly originates from smooth muscle cells in the vessel wall. 17,18 More recent models have suggested that A in CAA is predominantly generated by neurons [19][20][21] and subsequently deposited in the vessel wall because of impairment in A clearance. Impaired A clearance may be caused by alterations in perivascular drainage pathways [22][23][24] and deficits in endothelial-mediated active transport of A into the blood.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…23). Previous studies have established the ratio of Aβ40 to Aβ42 as an important factor in determining the fibrillogenesis, toxicity and pathological distribution of Aβ in vivo [58][59][60] . The ability to obtain monomeric and protofibril preparations of Aβ42 and Aβ40 by SEC allowed us to characterize the interactions between these two peptides at the levels of monomers, protofibrils and fibrils.…”
Section: High Molecular Weightmentioning
confidence: 99%